Desert ants use olfactory scenes for navigation. (August 2015) - Buehlmann, Cornelia; Graham, Paul; Hansson, Bill S.; Knaden, Markus
Abstract : Desert ants, Cataglyphis fortis, forage for dead arthropods in the Tunisian salt pans. Both the unpredictable food distribution and the high surface temperatures might account for the fact that the ants do not use any pheromone trails. However, Cataglyphis has been shown to still use olfactory cues for navigation. For instance, the ants locate sparsely distributed food or pinpoint their inconspicuous nest entrance by following odour plumes. In this study we found that, as well as using odours to pinpoint a target, the ants might use environmental odours as olfactory landmarks when following habitual routes. When analysing odours collected at 100 positions in the desert, we found spatially distinct gradients of a range of different environmental odorants. Furthermore we confirm that individual foragers followed forager-specific routes when leaving the nest. Therefore these ants could potentially learn such olfactory landscape features along their stable routes. We, hence, asked whether ants could learn and use olfactory cues for route guidance. We trained ants to visit a stable feeder and presented them with a sequence of four different odours along the way. Homing ants that had already passed the odour alley on their way back were displaced to a remote test field and released at the starting point of an identical alley. Control ants that experienced the alley only during the test situation focused their search on the release point. Ants that had experienced the odours during training, however, biased their nest search towards the odour alley and performed straight walking segments along the alley. Hence, we found that ants learnt the olfactory cues along their homeward route and used these cues in the absence of other navigational information. Hence, desert ants seem to be able to use odour information to follow routes. Highlights: The uncluttered desert provides odour features that might be used for navigation. Ants take consistent paths that enable them to learn spatial odour information. Desert ants can follow a route that is defined only by odour information.